Age is more than just a number: The relationship among age, non-chronological age factors, self-perceived driving abilities, and autonomous vehicle acceptance. (December 2022) - Huang, Gaojian; Hung, Ya-Hsin; Proctor, Robert W.; Pitts, Brandon J.
Highlights: Age, non-chronological age factors, and self-perceived driving abilities can influence autonomous vehicle acceptance. Self-perceived driving abilities (SPDA) were negatively associated with autonomous vehicle (AV) acceptance. For non-chronological age factors, older adults' perceived social support was positively associated with AV acceptance. Younger age and higher educational attainment indicated greater willingness to adopt AVs. Older adults reported lower AV acceptance but higher self-perceived driving abilities compared to younger adults. Abstract: Globally, adults aged 65 and older are a rapidly-growing population. Aging is associated with declines in perceptual, cognitive, and physical abilities, which often creates challenges in completing daily activities, such as driving. Autonomous vehicles (AVs) promise to provide older adults one way to maintain their mobility and independence. However, recent surveys of AV acceptance suggest that older adults have a lower AV acceptance compared to younger generations. One challenge is that most of these assessments have not accounted for the various non-chronological age factors that contribute to how older adults perceive their own driving skills and the utility of AVs. To fill this research gap, this study investigated the effects of non-chronological age factors and rated self-perceived driving abilities on AV acceptance across three age groups. An online survey was conducted using Amazon Mechanical Turk (MTurk), for which 438 valid responses were received. Respondents were categorized into a younger (18–40 years), middle-aged (41–64 years), and older (65–79 years) adult age group. Results showed that drivers of a younger age, with higher educational attainment, who rated themselves to have higher social support, and who have lower rated self-perceived driving abilities, report being more willing to accept AVs. Findings from this work can help to inform models of AV technology acceptance and guide in the development of marketing strategies to promote knowledge of AVs.